Levantamento de subsídios para os professores do ciclo I desenvolverem práticas pedagógicas no ensino da Matemática com alunos com deficiência nas escolas públicas - Santos, Regiane Silva dos (2013)
The present research is one of the products from the Research Project: Challenges for the inclusive education: thinking the teachers training through the processes of mastering Mathematics in the early grades of primary and secondary education. It has been approved by INEP/CAPES public notice n.38/10 Observatory of Education and is coordinated by Doctor Ana Lúcia Manrique, from the Program of Studies of postgraduate degrees in Mathematical Education of PUC-SP. Its main goal is to answer the following question: Which grants are offered to primary school teachers to develop pedagogical practices when teaching Mathematics to disabled students in public schools? To answer to such a question, a survey was carried out in three levels, national, state and municipal. The method used was the textual and documental analysis, which helped on the search, carrying out data and cataloguing them, thus, making a corpus. After the corpus constitution we categorized and established theme units in each level: National Programs and actions, Publications and the training and resource centers, State- Programs and Projects which reach not only the teacher but also the student; Municipal Programs, Projects and Publications. After doing the theme units we ve chosen one item from each level, naming the units of analysis, this means the checked and interpreted object of study upon the historical and critical conception of Dermeval Saviani, turning the constitution of the text possible. When the text was ready it was possible to analise and check if the programs, projects, publications, actions and centers, which were ruled by laws and decrees, offered grants for teachers to work with students with difficulties at Mathematics. We consider that there are a few proposals about specific subjects